1998
DOI: 10.1038/28179
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic induction of network oscillations at 40 Hz in the hippocampus in vitro

Abstract: Acetylcholine is vital for cognitive functions of the brain. Although its actions in the individual cell are known in some detail, its effects at the network level are poorly understood. The hippocampus, which receives a major cholinergic input from the medial septum/diagonal band, is important in memory and exhibits network activity at 40 Hz during relevant behaviours. Here we show that cholinergic activation is sufficient to induce 40-Hz network oscillations in the hippocampus in vitro. Oscillatory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

76
857
2
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 832 publications
(942 citation statements)
references
References 29 publications
76
857
2
7
Order By: Relevance
“…16,17,19,37 Rodent hippocampal slices express various patterns of naturally occurring network oscillations and permit high-resolution recordings with electrophysiological methods, live-cell imaging techniques and oxygen sensor microelectrodes under well-defined recording conditions. [38][39][40][41] This in vitro preparation also provides a reasonable model for examining energy metabolism during different forms of neuronal network activation. [42][43][44][45] In the hippocampal slices, persistent gamma oscillations can be reliably induced by bath application of cholinergic or glutamatergic receptor agonists at nanomolar to low micromolar concentrations ( Figures 1A and 1B).…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17,19,37 Rodent hippocampal slices express various patterns of naturally occurring network oscillations and permit high-resolution recordings with electrophysiological methods, live-cell imaging techniques and oxygen sensor microelectrodes under well-defined recording conditions. [38][39][40][41] This in vitro preparation also provides a reasonable model for examining energy metabolism during different forms of neuronal network activation. [42][43][44][45] In the hippocampal slices, persistent gamma oscillations can be reliably induced by bath application of cholinergic or glutamatergic receptor agonists at nanomolar to low micromolar concentrations ( Figures 1A and 1B).…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%
“…The most widespread models use acetylcholine or carbachol for activation of metabotropic cholinergic receptors, or kainate (kainic acid) for activation of ionotropic glutamatergic receptors. 40,41,46,47 Pharmacologically induced hippocampal gamma oscillations in vitro are most prominent in the neuronal network of subfield CA3, weaker in subfield CA1, and less prominent or absent in the dentate gyrus. 16,41 They can occur in the presence or in the absence of theta oscillations, 40,41 similar to the pattern of gamma oscillations in vivo.…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hippocampus, the spike of one basket cell can synchronize the activity of a large number of pyramidal cells 109 . Inhibitory cells are involved in the generation of fast oscillations, especially those in the gamma frequency range 110,111 . Consistent with this role, for in vivo recordings the power spectrum of currents generated by inhibitory synapses has more power in the gamma frequency range than the power spectrum of currents generated by excitatory synapses 112 .…”
Section: Inhibition Can Modulate Firing Rate and Influence Spike Timesmentioning
confidence: 99%
“…At the circuit level, cholinergic modulation appears to control the frequency content and the coherence of cortical oscillations. For example gamma-band synchronized oscillations are observed under increased cholinergic levels in the cortex (Rodriguez et al 2004) In vitro, experiments have shown that cholinergic antagonists promote synchronized high frequency oscillatory activity Fisahn et al 1998). This suggests that acetylcholine has a significant modulatory control over the emergence of rhythmic activity in cortical circuits.…”
Section: Introductionmentioning
confidence: 99%